Guidelines for the use of diagnostic imaging in musculoskeletal pain conditions affecting the lower back, knee and shoulder: A scoping review. (4th August 2020) - Cuff, Andrew; Parton, Stephen; Tyer, Robert; Dikomitis, Lisa; Foster, Nadine; Littlewood, Chris
Abstract: Background: Musculoskeletal (MSK) pain is one of the most common reasons for primary care consultation, particularly pain in the lower back (LBP), knee and shoulder. The use of diagnostic imaging for MSK pain is increasing, but it is unclear whether this increase is justified on the basis of clinical practice guideline (CPG) recommendations. Aim: To identify and map the content of CPGs that informs the use of diagnostic imaging in those with nontraumatic LBP, knee and shoulder pain in primary and intermediate care in the UK. Design and Setting: A scoping review of CPGs. Methods: This scoping review was conducted and is reported in accordance with PRISMA guidance. A broad search strategy included electronic searches of MEDLINE, CINAHL, PsychINFO and SPORTDiscus from 2009 to 17 April 2019. This was conducted alongside a search of guideline repositories and was combined with a snowball search of Google, relevant professional bodies and use of social media. Results: 31 relevant CPGs were included. Routine use of diagnostic imaging for those with nontraumatic LBP, knee or shoulder pain is generally discouraged in primary care or intermediate care. Diagnostic imaging should be reserved for when specific or serious pathology is suspected or where the person is not responding to initial nonsurgical management and the imaging result is expected to change clinical management decisions. Conclusion: Diagnostic imaging should not be routinely requested in primary or intermediate care for nontraumatic LBP, knee or shoulder pain. CPGs do not justify the increasing imaging rates in the UK for MSK pain.